Model Keluarga dan Interelasinya di tengah Derasnya Arus Zaman (Eksposisi Efesus 5: 22-6:1-4) - Stephanus Hartoyo (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
Having observed through media as well as current events in our society, the writer is quite concerned for the family life and future of the next generation. Permissiveness and unfaithfulness are very common in society today, the rate of divorce is getting higher and higher. While violence and crime are prevalent among the youth of today; home to some extent, has lost its function. The interrelationship among the family members has decreased in quality and quantity. Ephesians 5:22-6:4 provides helpful answers and solutions, especially for believers in Jesus Christ. That text helps us to maintain a healthy and successful family as well as nurture our children mentally and spiritually.